Difference between revisions of "Terrain-Following Coordinate Transformation"

From WikiROMS
Jump to navigationJump to search
(convert to TeX)   (change visibility)
Line 1: Line 1:
<div class="title">Vertical Terrain-Following Coordinates</div>
<div class="title">Vertical Terrain-Following Coordinates</div>
<wikitex>


From the point of view of the computational model, it is highly
From the point of view of the computational model, it is highly
convenient to introduce a stretched vertical coordinate system which
convenient to introduce a stretched vertical coordinate system which
essentially "flattens out" the variable bottom at <math>z = -h(x,y)\!\,</math>.
essentially "flattens out" the variable bottom at $z = -h(x,y)$.
Such "<math>s\!\,</math>" coordinate systems have long been used, with slight
Such "$s$" coordinate systems have long been used, with slight
appropriate modification, in both meteorology and oceanography
appropriate modification, in both meteorology and oceanography
[e.g., Phillips (1957) and Freeman et al. (1972)].
[e.g., Phillips (1957) and Freeman et al. (1972)].
To proceed, we make the coordinate transformation:
To proceed, we make the coordinate transformation:


:<math> \hat{x} = x</math>
$$\hat{x} = x$$
:<math> \hat{y} = y </math>
$$\hat{y} = y $$
:<math> s = s(x,y,z)\!\,</math>
$$s = s(x,y,z)$$
:<math> z = z(x,y,s)\!\,</math>
$$z = z(x,y,s)$$
:<math> \hat{t} = t</math>
$$\hat{t} = t$$


See [[S-coordinate]] for the form of <math>s\!\,</math> used here.
See [[S-coordinate]] for the form of $s$ used here.
In the stretched system, the vertical coordinate <math>s\!\,</math> spans the
In the stretched system, the vertical coordinate $s$ spans the
range <math>-1 \leq s \leq 0\!\,</math>; we are therefore left with
range $-1 \leq s \leq 0$; we are therefore left with
level upper (<math>s = 0\!\,</math>) and lower (<math>s = -1\!\,</math>) bounding
level upper ($s = 0$) and lower ($s = -1$) bounding
surfaces.  The chain rules for this transformation are:
surfaces.  The chain rules for this transformation are:


:<math>\left( { \partial \over \partial x } \right)_z =\left( { \partial \over \partial x } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial x } \right)_s { \partial \over \partial s}</math>
$$\left( { \partial \over \partial x } \right)_z =\left( { \partial \over \partial x } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial x } \right)_s { \partial \over \partial s}$$


:<math>\left( { \partial \over \partial y } \right)_z = \left( { \partial \over \partial y } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial y } \right)_s { \partial \over \partial s}</math>
$$\left( { \partial \over \partial y } \right)_z = \left( { \partial \over \partial y } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial y } \right)_s { \partial \over \partial s}$$


:<math>{ \partial \over \partial z } = \left( { \partial s \over \partial z } \right) { \partial \over \partial s} =  { 1 \over H_z } { \partial \over \partial s }</math>
$${ \partial \over \partial z } = \left( { \partial s \over \partial z } \right) { \partial \over \partial s} =  { 1 \over H_z } { \partial \over \partial s }$$


where
where


:<math>H_z \equiv { \partial z \over \partial s }</math>
$$H_z \equiv { \partial z \over \partial s }$$


As a trade-off for this geometric
As a trade-off for this geometric
Line 36: Line 38:
carats:
carats:


:<math>{\partial u \over \partial t} - fv + \vec{v} \cdot \nabla u = - {\partial \phi \over \partial x} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial x} - g {\partial \zeta \over \partial x} + {F}_u + {D}_u</math>
$${\partial u \over \partial t} - fv + \vec{v} \cdot \nabla u = - {\partial \phi \over \partial x} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial x} - g {\partial \zeta \over \partial x} + {\cal F}_u + {\cal D}_u$$
 
:<math>\frac{\partial v}{\partial t} + fu + \vec{v} \cdot \nabla v = - \frac{\partial \phi}{\partial y} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial y} - g {\partial \zeta \over \partial y} + {F}_v + {D}_v</math>


:<math>\frac{\partial T}{\partial t} + \vec{v} \cdot \nabla T = {F}_{T} + {D}_{T}</math>
$$\frac{\partial v}{\partial t} + fu + \vec{v} \cdot \nabla v = - \frac{\partial \phi}{\partial y} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial y} - g {\partial \zeta \over \partial y} + {\cal F}_v + {\cal D}_v$$


:<math>\frac{\partial S}{\partial t} + \vec{v} \cdot \nabla S = {F}_{S} + {D}_{S}</math>
$$\frac{\partial T}{\partial t} + \vec{v} \cdot \nabla T = {\cal F}_{T} + {\cal D}_{T}$$


:<math>\rho = \rho(T,S,P)\!\,</math>
$$\frac{\partial S}{\partial t} + \vec{v} \cdot \nabla S = {\cal F}_{S} + {\cal D}_{S}$$


:<math>\frac{\partial \phi}{\partial s} = \left( \frac{-gH_z\rho} {\rho_o} \right)</math>
$$\rho = \rho(T,S,P)$$


:<math>{\partial H_z \over \partial t} + {\partial (H_zu) \over \partial x} + {\partial (H_zv) \over \partial y} + {\partial (H_z \Omega) \over \partial s} = 0</math>
$$\frac{\partial \phi}{\partial s} = \left( \frac{-gH_z\rho} {\rho_o} \right)$$


$${\partial H_z \over \partial t} + {\partial (H_zu) \over \partial x} + {\partial (H_zv) \over \partial y} + {\partial (H_z \Omega) \over \partial s} = 0$$
where
where


:<math>\vec{v} = (u,v,\Omega)</math>
$$\vec{v} = (u,v,\Omega)$$


:<math>\vec{v} \cdot \nabla = u \frac{\partial}{\partial x} + v
$$\vec{v} \cdot \nabla = u \frac{\partial}{\partial x} + v
   \frac{\partial}{\partial y} + \Omega \frac{\partial}{\partial s}</math>
   \frac{\partial}{\partial y} + \Omega \frac{\partial}{\partial s}$$


The vertical velocity in <math>s\!\,</math> coordinates is
The vertical velocity in $s$ coordinates is


:<math>\Omega (x,y,s,t) = {1 \over H_z} \left[ w - (1+s) {\partial \zeta \over \partial t} - u {\partial z \over \partial x} - v {\partial z \over \partial y} \right]</math>
$$\Omega (x,y,s,t) = {1 \over H_z} \left[ w - (1+s) {\partial \zeta \over \partial t} - u {\partial z \over \partial x} - v {\partial z \over \partial y} \right]$$


and
and


:<math>w = {\partial z \over \partial t} + u {\partial z \over \partial x}
$$w = {\partial z \over \partial t} + u {\partial z \over \partial x}
   + v {\partial z \over \partial y} + \Omega H_z</math>
   + v {\partial z \over \partial y} + \Omega H_z$$


==Vertical Boundary Conditions==
==Vertical Boundary Conditions==
Line 71: Line 72:
become:
become:


top (<math>s = 0\!\,</math>):
top ($s = 0$):
::<math>\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_s (x,y,t)</math>
::$\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_s (x,y,t)$
::<math>\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_s(x,y,t)</math>
::$\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_s(x,y,t)$
::<math>\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = {Q_T \over \rho_o c_P}  + {1 \over \rho_o c_P} {dQ \over dT} (T - T_{\rm ref})</math>
::$\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = {Q_T \over \rho_o c_P}  + {1 \over \rho_o c_P} {dQ \over dT} (T - T_{\rm ref})$
::<math>\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = {(E - P) S \over \rho_o}</math>
::$\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = {(E - P) S \over \rho_o}$
::<math>\Omega = 0\!\,</math>
::$\Omega = 0$


and bottom (<math>s = -1\!\,</math>):
and bottom ($s = -1$):
::<math>\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_b (x,y,t)</math>
::$\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_b (x,y,t)$
::<math>\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_b (x,y,t)</math>
::$\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_b (x,y,t)$
::<math>\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = 0</math>
::$\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = 0<$
::<math>\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = 0 </math>
::$\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = 0$
::<math>\Omega = 0\!\,</math>
::$\Omega = 0$


Note the simplification of the boundary conditions on vertical
Note the simplification of the boundary conditions on vertical
velocity that arises from the <math>s\!\,</math> coordinate transformation.
velocity that arises from the $s$ coordinate transformation.

Revision as of 00:48, 10 July 2008

Vertical Terrain-Following Coordinates

<wikitex>

From the point of view of the computational model, it is highly convenient to introduce a stretched vertical coordinate system which essentially "flattens out" the variable bottom at $z = -h(x,y)$. Such "$s$" coordinate systems have long been used, with slight appropriate modification, in both meteorology and oceanography [e.g., Phillips (1957) and Freeman et al. (1972)]. To proceed, we make the coordinate transformation:

$$\hat{x} = x$$ $$\hat{y} = y $$ $$s = s(x,y,z)$$ $$z = z(x,y,s)$$ $$\hat{t} = t$$

See S-coordinate for the form of $s$ used here. In the stretched system, the vertical coordinate $s$ spans the range $-1 \leq s \leq 0$; we are therefore left with level upper ($s = 0$) and lower ($s = -1$) bounding surfaces. The chain rules for this transformation are:

$$\left( { \partial \over \partial x } \right)_z =\left( { \partial \over \partial x } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial x } \right)_s { \partial \over \partial s}$$

$$\left( { \partial \over \partial y } \right)_z = \left( { \partial \over \partial y } \right)_s - \left( { 1 \over H_z } \right) \left( { \partial z \over \partial y } \right)_s { \partial \over \partial s}$$

$${ \partial \over \partial z } = \left( { \partial s \over \partial z } \right) { \partial \over \partial s} = { 1 \over H_z } { \partial \over \partial s }$$

where

$$H_z \equiv { \partial z \over \partial s }$$

As a trade-off for this geometric simplification, the dynamic equations become somewhat more complicated. The resulting dynamic equations are, after dropping the carats:

$${\partial u \over \partial t} - fv + \vec{v} \cdot \nabla u = - {\partial \phi \over \partial x} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial x} - g {\partial \zeta \over \partial x} + {\cal F}_u + {\cal D}_u$$

$$\frac{\partial v}{\partial t} + fu + \vec{v} \cdot \nabla v = - \frac{\partial \phi}{\partial y} - \left( \frac{g\rho} {\rho_o} \right) \frac{\partial z}{\partial y} - g {\partial \zeta \over \partial y} + {\cal F}_v + {\cal D}_v$$

$$\frac{\partial T}{\partial t} + \vec{v} \cdot \nabla T = {\cal F}_{T} + {\cal D}_{T}$$

$$\frac{\partial S}{\partial t} + \vec{v} \cdot \nabla S = {\cal F}_{S} + {\cal D}_{S}$$

$$\rho = \rho(T,S,P)$$

$$\frac{\partial \phi}{\partial s} = \left( \frac{-gH_z\rho} {\rho_o} \right)$$

$${\partial H_z \over \partial t} + {\partial (H_zu) \over \partial x} + {\partial (H_zv) \over \partial y} + {\partial (H_z \Omega) \over \partial s} = 0$$ where

$$\vec{v} = (u,v,\Omega)$$

$$\vec{v} \cdot \nabla = u \frac{\partial}{\partial x} + v

 \frac{\partial}{\partial y} + \Omega \frac{\partial}{\partial s}$$

The vertical velocity in $s$ coordinates is

$$\Omega (x,y,s,t) = {1 \over H_z} \left[ w - (1+s) {\partial \zeta \over \partial t} - u {\partial z \over \partial x} - v {\partial z \over \partial y} \right]$$

and

$$w = {\partial z \over \partial t} + u {\partial z \over \partial x}

 + v {\partial z \over \partial y} + \Omega H_z$$

Vertical Boundary Conditions

In the stretched coordinate system, the vertical boundary conditions become:

top ($s = 0$):

$\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_s (x,y,t)$
$\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_s(x,y,t)$
$\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = {Q_T \over \rho_o c_P} + {1 \over \rho_o c_P} {dQ \over dT} (T - T_{\rm ref})$
$\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = {(E - P) S \over \rho_o}$
$\Omega = 0$

and bottom ($s = -1$):

$\left(\frac{K_m}{H_z}\right) \frac{\partial u}{\partial s} = \tau^x_b (x,y,t)$
$\left(\frac{K_m}{H_z}\right) \frac{\partial v}{\partial s} = \tau^y_b (x,y,t)$
$\left(\frac{K_T}{H_z}\right) \frac{\partial T}{\partial s} = 0<$
$\left(\frac{K_S}{H_z}\right) \frac{\partial S}{\partial s} = 0$
$\Omega = 0$

Note the simplification of the boundary conditions on vertical velocity that arises from the $s$ coordinate transformation.